2015
DOI: 10.4025/actasciagron.v37i3.19573
|View full text |Cite
|
Sign up to set email alerts
|

<b>Cryopreservation of the mangaba tree (<em>Hancornia speciosa</em> Gomes): a protocol for long-term storage

Abstract: ABSTRACT. The aim of this study was to evaluate the efficiency of vitrification and droplet vitrification for the cryopreservation of Hancornia speciosa shoot tips. The shoot tips were subjected to four different periods of exposure (15, 30, 45 and 60 min.) to plant vitrification solution 2 (PVS2) before plunging into liquid nitrogen. We evaluated the regrowth of H. speciosa shoot tips that were cryopreserved by the classical vitrification technique and by the droplet vitrification technique. Shoot tips were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…It presents, predominantly, zoochory dispersion, with the hoary fox (Lycalopex vetulus) being one of its dispersers (Dalponte;Lima, 1999). The seeds are recalcitrant, and the propagation by asexual pathways is uncommon (Santos et al, 2015), which hinders the production of seedlings and natural regeneration.…”
Section: Target Speciesmentioning
confidence: 99%
“…It presents, predominantly, zoochory dispersion, with the hoary fox (Lycalopex vetulus) being one of its dispersers (Dalponte;Lima, 1999). The seeds are recalcitrant, and the propagation by asexual pathways is uncommon (Santos et al, 2015), which hinders the production of seedlings and natural regeneration.…”
Section: Target Speciesmentioning
confidence: 99%
“…Some authors have already described research works with the cryopreservation technique applied to lateral buds and apical meristems of mangaba tree. Efficient results have been reported with the droplet vitrification and vitrification techniques with more than 70% regeneration of shoot tips after cryopreservation [12]. Using the droplet vitrification technique, the same authors obtained 90% shoot tip growth resumption.…”
Section: Introductionmentioning
confidence: 88%
“…In addition, studies have reported that the leaf extract has antihypertensive and vessel dilator effects (Pereira et al, 2012), whereas the latex has anti-inflammatory properties (Marinho et al, 2011). Due to the high economic and medicinal potential this species has been widely used in the reforestation programs of the Cerrado region (Santos et al, 2015;Almeida et al, 2016). Biometric characterization consists in evaluating morphological traits of different parts of the plant, such as fruits and seeds, or of the plant as a whole (Silva et al, 2017a).…”
Section: Introductionmentioning
confidence: 99%
“…The use of seeds is the most widely used method for the propagation of mangaba plants. However, as this species produces recalcitrant seeds, the sexual propagation is hampered (Santos et al, 2015). Therefore, the success of seed utilization depends on a rapid and uniform emergence of seedlings in the nursery or field (Barros et al, 2010;Vieira et al, 2015).…”
Section: Introductionmentioning
confidence: 99%